Pengaruh Pemberian Edukasi Apoteker Terhadap Tingkat Pengetahuan Masyarakat Tentang DAGUSIBU di Kabupaten Bantul - Shalahuddin Al Madury; Arifah, Mitsalina Fildzah; Maulana, M. Fadlhil Rheza (Jurnal Indonesia Sehat, 2024)
Background: Medication error among the community is a major public health problem that can cause great harm to patients. Problems that are often found in the community are the level of understanding of drug use starting from obtaining, using, storing, and destruction of drugs in the correct way. Sustainable efforts are needed to improve public knowledge through the provision of information through educational media by Pharmacists as health workers who understand drugs. Purpose:  This study aims to determine the effect of Pharmacist education on the level of public knowledge in Bantul Regency. Method:  This type of research is pre-experimental with a one group pre-test, post-test design in one group. Analysis using univariate and bivariate using the Wilcoxon test. Result:  The results showed an increase in the percentage of respondents' knowledge level in the good category after receiving educational treatment with the lecture method and assisted by leaflet media, from 27.5% to 52.5%, and a decrease in the level of knowledge is less, at the pre-test 27.5% to 15% during the post-test conducted after education was carried out. Conclusion:  The provision of education materials by pharmacists has a significant effect on increasing knowledge about DAGUSIBU in the community in Bantul Regency with a p-value (0.021) <0.05.